Influence of global warming on the growth of dwarf shrubs in the French Alps : dendroecological analysis of Rhododendron ferrugineum L. in contrasting topoclimatic contexts - Francon, Loïc (HAL CCSD, 2020)
Alpine ecosystems, such as the Arctic tundra, are experiencing a pronounced warming compared to the rest of the world. In the Arctic, dendroecological studies have documented the climatic drivers of the expansion of dwarf shrubs. These changes in the Arctic tundra have far-reaching implications for albedo, snow cover, soil, ground-level microclimate, global carbon cycle and climate. The European Alps have warmed considerably in recent decades, and this has occurred in a non-linear way, with an inflection point the end of the 1980s. Since then, summer temperature has sharply increased and snow cover durability in spring has declined. By analogy with the Arctic, we hypothesize that at high elevation, the decrease in climatic constraints (increase in summer temperatures, decrease in snow cover duration) favors an increase in shrubs radial growth. In order to validate this hypothesis, eight populations of Rhododendron ferrugineum L. (Ericaceae) were collected in the French Alps, throughout a network designed to be representative of the contrasts in continentality, elevation and slope aspect across the French Alps. Classical statistical procedures used in dendroecology (Correlation functions) and models traditionally used in ecology (Structural Equation Models, Linear Mixed Models, SEMs, LMMs) have been coupled to finely assess the relationships between the radial growth of R. Ferrugineum and nivo-meteorological variables.The first chapter shows the dendroecological potential of R. Ferrugineum in a population (2000 m asl) from the Taillefer massif. Correlation function analyses reveal that winter precipitation and summer temperature act as main co-limiting factors for shrub growth while comparable sensitivity to snowfall was not observed in a population of adjacent trees (P. abies). In chapter 2, two additional R. ferrugineum plots were sampled in the Taillefer massif at 1800 and 2400 m asl. The radial growth of R. ferrugineum along the elevation gradient was compared to local re-analyses from the SAFRAN-crocus ...